1994
DOI: 10.1111/j.1365-2648.1994.tb01137.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional experiences, empathy and burnout among staff caring for demented patients at a collective living unit and a nursing home

Abstract: Experiences of empathy and burnout were compared among staff caring for demented patients, at a collective living unit (n = 10) and a nursing home (n = 10) in the middle of Sweden. In both milieus, the staff showed great confidence in their own caring ability and disclosed a deep care and concern for their patients. All staff had the requisite attributes of empathy, and none had burnout scores indicating risk of burnout. The staff of the collective living unit gave exclusively positive descriptions of their pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 10 publications
2
56
0
1
Order By: Relevance
“…Green House: Rabig et al, 2006;Angelelli, 2006;Kane et al, 2007. Group Home : Funaki et al, 2005;Hirakawa et al, 2006;Nakanishi and Honda, 2008;Yokota et al, 2006;Onishi et al, 2006. Group Living: Annerstedt, 19931997;Annerstedt et al, 1993a;1993b;1996;2000;Andren and Elmstahl, 2002;2007;Ahlund, 1999;Alfredson and Annerstedt, 1994;Elmstahl et al, 1997;1998a;1998b;Faxen-Irving et al, 2002;Jensen et al, 2002;Kihlgren et al, 1992;Kuremyr et al, 1994;Malmberg and Zarit, 1993;Marshall, 1993;Norbergh et al, 2001;2002;Radzey et al, 2001;Sandman and Wallblom, 1996;Svensson et al, 1996;Wimo et al, 1991;1995a;1995b;1995c;Wimo and Morthenson Ekelöf, 2004. Residential groups: Radzey et al, 2001;Reggentin and Dettbarn-Reggentin, 2004a;2004b;Leichsenring et al, 1998;Dettbarn-Reggentin, 2005.…”
Section: Residents' Characteristicsmentioning
confidence: 96%
“…Green House: Rabig et al, 2006;Angelelli, 2006;Kane et al, 2007. Group Home : Funaki et al, 2005;Hirakawa et al, 2006;Nakanishi and Honda, 2008;Yokota et al, 2006;Onishi et al, 2006. Group Living: Annerstedt, 19931997;Annerstedt et al, 1993a;1993b;1996;2000;Andren and Elmstahl, 2002;2007;Ahlund, 1999;Alfredson and Annerstedt, 1994;Elmstahl et al, 1997;1998a;1998b;Faxen-Irving et al, 2002;Jensen et al, 2002;Kihlgren et al, 1992;Kuremyr et al, 1994;Malmberg and Zarit, 1993;Marshall, 1993;Norbergh et al, 2001;2002;Radzey et al, 2001;Sandman and Wallblom, 1996;Svensson et al, 1996;Wimo et al, 1991;1995a;1995b;1995c;Wimo and Morthenson Ekelöf, 2004. Residential groups: Radzey et al, 2001;Reggentin and Dettbarn-Reggentin, 2004a;2004b;Leichsenring et al, 1998;Dettbarn-Reggentin, 2005.…”
Section: Residents' Characteristicsmentioning
confidence: 96%
“…Across care settings organizational factors impacted patient care: policies (such as individualized care plans or meal choices) appearing only on paper and not in practice; lack of infrastructure; difficulty with system navigation/coordination; poor support from management; and poor organization in the workplace. (29,34,38,48) Rural physicians also described difficulties with access to resources. (28) Staff reported that long-term care policies, such as moving later-stage patients to separate wards, caused stress to both workers and patients.…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative examination of the experiences of staff caring for older people is now appearing in the literature (Kuremyr et al 1994, Dunn et al 1994. The work milieu can be a valuable resource in buffering stress and burnout in residential care.…”
Section: Discussionmentioning
confidence: 98%